Genetics of hereditary motor and sensory neuropathy and the Costa Rican contribution - Alejandro Leal (Revista de Biología Tropical, 2004)
Hereditary motor and sensory neuropathy (HMSN) or Charcot-Marie-Tooth disease (CMT) is the most common hereditary illness of the peripheral nervous system. The genetics and the physiopathological aspects of the disease clarified until know, are here summarized. More than twenty genes and ten additional loci have been related with HMSN. These findings contribute to understand the metabolism of peripheral nerves and give the basis for molecular diagnostics and future therapy. Several Costa Rican families with CMT have been identified, specially with axonal forms. Two families present mutations in the myelin protein zero gene (MPZ). In addition, linkage have been found between the disease and locus 19q13.3 in an extended family, and a mutation segregating with the disease is present in a candidate gene of the critical interval. Costa Rica has several advantages for genetical studies, that can contribute importantly in the generation of knowledge in the neurogenetical field. Rev. Biol. Trop. 52(3): 475-483. Epub 2004 Dic 15. El grupo de neuropatías motoras y sensoriales hereditarias (HMSN) o enfermedad de Charcot-Marie-Tooth (CMT) es el padecimiento hereditario más común del sistema nervioso periférico. El propósito de este trabajo es resumir los aspectos genéticos y fisiopatológicos más actuales de esta enfermedad. Más de veinte genes y diez loci adicionales han sido relacionados con HMSN. Estos hallazgos han contribuido con la comprensión del metabolismo de los nervios periféricos y sirven de base para el diagnóstico molecular y el diseño de terapias. Diversas familias costarricenses con CMT han sido identificadas: dos de ellas presentan mutaciones en el gen que codifica por la mielina proteína cero (MPZ). Además, un análisis de ligamiento localizó el gen que causa una forma axonal de la enfermedad en el cromosoma 19q13.3 en una extensa familia; también se detectó en esa región una mutación que co-segrega con la enfermedad y que modifica la secuencia de un gen candidato. Costa Rica presenta numerosas ventajas para estudios genéticos, que pueden contribuir en la generación de conocimiento en el área de la neurogenética.